N,N′-Bis[3,5-bis(2,6-diisopropylphenyl)phenyl]butane-2,3-diimine - Lohr, Tracy L. (International Union of Crystallography, 2011)
The title molecule, C(64)H(80)N(2), lies on an inversion center wherein the central butanediimine fragment [N=C(Me)—C(Me)=N] is essentially planar [maximum deviation = 0.002 (2) Å] and its mean plane forms a dihedral of 70.88 (10)° with the attached benzene ring. In the symmetry-unique part of the molecule, the dihedral angles between the benzene ring bonded to the N atom and the other two benzene rings are 89.61 (6) and 82.77 (6)°.